Sap flow density and hydraulic conductivity of three mature exotic forest species under similar planting condition - Alagapan, Tharani (2019)
Water is the most vital element for any living organism especially for trees. It plays a major role in regulating the daily biochemical process that responds physiologically towards soil and atmospheric factors. Water requirement of species is an essential measure for the tree’s survival and adaptation in a particular environment especially for exotic species. The aim of this study is to determine sap flow and hydraulic conductivity of three mature exotic species belonging to the same site. Relationship of sap flow and hydraulic conductivity with climate factors were also assessed. Data was collected for duration of eight months in Randomized Incomplete Block Design (RIBD) using three different mature exotic species; Gmelina arborea (Yemane), Swietenia macrophylla (Mahogany) and Pinus caribaea (Pine). Judgement and simple random sampling were used to select the samples from the site at Universiti Putra Malaysia (UPM) with the support of random number generator. Thermal Dissipation Probe (TDP) was used as the main equipment and supported by pressure chamber together with other tools while climatic data were obtained from Faculty of Environmental Studies, UPM and Sultan Idris Shah Forestry Education Center (SISFEC) weather station. Research findings indicated that Pine species had the highest sap flow density and hydraulic conductivity by mean value of 950.052 (±45.096) g/day and 9.086 (±0.413) kg/m²/day/MPa respectively. Meanwhile, Mahogany showed the lowest sap flow density and hydraulic conductivity which are 232.074(±9.150) g/day and 0.330 (±0.022) kg/m²/day/MPa respectively. Closest positive association at 96.8% is between Pine’s sap flow and hydraulic conductivity which is significantly different as indicated from p-value of less than 0.0001. Temperature and relative humidity have slightly contributed to the water system of Pine. Current results revealed that water potential, sapwood and leaf area were identified to have significant role in regulating the sap flow density and hydraulic conductivity. Tree height, structure, type of leaf and different structure of tracheid and vessels have contribute to the water system of trees and been the crucial factor for the whole phenomena of sap flux and biochemical process of the tree. Thus, sap flow study is an important process in evaluating water consumption of tree species and should be carried out on potential native species which can be helpful in species selection, planning and establishment of forest plantation.